The concerntration of heavy metals in selected clay samples in ekiti state, southwestern Nigeria (2011)
"The presence and possible effect of heavy metal (such as cadmium, zinc, lead, e.t.c) concentration in the clay used in pot making were investigated. Clay samples were collected at three locations where they are used mostly in making pots and other kitchen utensils. The concentrations of heavy metals were determined using the Atomic Absorption Spectrometer (AAS). Results indicate that the concentration Cu, Zn, Cr, Pb, As, and Mn falls within the range of the maximum admissible concentration of heavy metals of several countries mostly in Europe. However, the concentration Cadmium and Nickel are relatively higher than the maximum admissible concentration of toxic metals in soil for countries like Denmark and Sweden."